2012
DOI: 10.1021/jp212254g
|View full text |Cite
|
Sign up to set email alerts
|

Diarylfluorene-Modified Fulleropyrrolidine Acceptors to Tune Aggregate Morphology for Solution-Processable Polymer/Fullerene Bulk-Heterojunction Solar Cells

Abstract: A series of n-type fulleropyrrolidine derivatives as the acceptors, including Th-C60, PFTh-C60, and OPFTh-C60, have been synthesized via the key step of the typical Prato reaction to investigate the steric hindrance effect of various phenylfluorenyl moieties on the electronic structures, aggregate morphologies, and device performances of solar cells. Conjugation-interrupted linkage obviously does not change the energy bandgaps and lowest unoccupied molecular orbital (LUMO) energy levels in PFTh-C60 and OPFTh-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…6B and C). As shown in Tables 2 and 3, before the inverted devices were annealed, the changing trend of Voc was as same as that of the LUMO levels, which showed that the Voc was related to the difference between the HOMO level of the p-type polymer and the LUMO level of the ntype fullerene derivatives [27][28][29]. In the cases of OIHC60P and OIMC60P, the Voc values decreased after the devices were annealed in air, which was probably because the annealing treatment induced the phase separation increasing ( Fig.…”
Section: Photovoltaic Propertiesmentioning
confidence: 66%
See 2 more Smart Citations
“…6B and C). As shown in Tables 2 and 3, before the inverted devices were annealed, the changing trend of Voc was as same as that of the LUMO levels, which showed that the Voc was related to the difference between the HOMO level of the p-type polymer and the LUMO level of the ntype fullerene derivatives [27][28][29]. In the cases of OIHC60P and OIMC60P, the Voc values decreased after the devices were annealed in air, which was probably because the annealing treatment induced the phase separation increasing ( Fig.…”
Section: Photovoltaic Propertiesmentioning
confidence: 66%
“…Furthermore, the addition of different substitute group on pyrrolidine ring did not induce significant changes of the energy band gap, which was due to the conjugation-interrupted linkage of the substitute group on fulleropyrrolidine ring [29]. Fig.…”
Section: Optical Propertiesmentioning
confidence: 81%
See 1 more Smart Citation
“…The multi-levelled molecular substructures of PF derivatives, such as dialkylfluorenes (F-I), heterofluorenes (F-II) [32][33][34], fused or curved fluorenes (F-III) [35], diarylfluorenes (F-IV) [36,37] and spirofluorenes (F-V) [38,39] (figure 1), have become an ideal platform to demonstrate the four-element principle that contains the p-n covalent design (also called the D-A design) [40][41][42][43], steric design [44,45], conformation and topology design [15,[46][47][48] and supramolecular interaction [25,31,49,50]. Previously, many efforts have been made to clarify low-energy green emission bands (also called g-bands) in PF-based electroluminescent thin films for application in high-performance devices [86].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperbranched conjugationinterrupted polymers have been made by means of Friedel-Crafts polymerization [26,27]. More recently, morphologydirected molecular designs have been demonstrated using diarylfluorene-modified fullerenes for bulk heterojunction solar cells by our group [28]. Series of works from XIE-HUANG group demonstrate that this approach is effective for function-directed semiconducting materials in organic electronics.…”
mentioning
confidence: 99%